The Students Willingness and Learning Attitudes Toward Speaking Skill - Angelika Rouli Sinaga (Juliet, 2021)
The purpose of this research is to find out whether or not there was a correlation between the students’ willingness to communicate, and learning attitudes toward speaking skill. This research used a quantitative correlation to find the relationship between the variables. This study’s population consisted of 147 students. The purposive sampling method was used to obtain the sample for this study, which consisted of 25 students from XI IPS 2 and XI IPS 3 classes. The instruments used to obtain data were questionnaires and online test. The questionnaire utilizes a google form with 10 statements and five answers in each statement to assess students’ willingness to communicate, and learning attitudes. The second, test is to obtain the results of each student’s speaking skill, which are recorded. Normality test, homogeneity test, linearity test, bivariate test, multiple correlation equation, and hypothesis test are used to analyze data. Based on data analysis, the multiple regression equation obtained 1.14, implying that there is a very strong relationship between willingness to communicate, and learning attitudes toward speaking skills.